A note on Muraena alba Zuiew, 1793 (Teleostei: Synbranchidae) - Britz, Ralf; Kottelat, Maurice; Kullander, Sven (Zootaxa, 2021)
Originally described as Muraena alba by the Russian ichthyologist Basilius Zuiew (1793) [Vasilij Fyodorovich Zuev’], the name Monopterus albus has long been used for a species of swamp eel (Synbranchidae) with a reportedly widespread occurrence in Asia (Rosen & Greenwood 1976, Kottelat 2013). In recent years molecular studies have shown that Monopterus albus of authors is a species complex and several authors have recommended that up to three (Collins et al. 2002, Matsumoto et al. 2010, Kottelat 2013, Nico et al. 2019) or even five (Arisuryanti 2016) different species can be recognized. Kottelat (2013) referred to the eastern Asian clade of Matsumoto et al. (2010) as Monopterus albus and the Southeast Asian clade as Monopterus javanensis La Cepède, 1800, noting that no name is available for the clade on the Ryukyu Islands.